INOVASI, KEPERCAYAAN, DAN ELECTRONIC WORD OF MOUTH UNTUK MENDORONG MINAT BERKUNJUNG WISATAWAN PANTAI GEMAH TULUNGAGUNG - Nafis, Raihan Wishal (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2021)
This research was conducted to reveal the behavior of tourists in terms of their decision to visit Gemah Beach in Tulungagung. This research can be used by the tourism manager of Gemah Beach to understand what is most important for tourists. Innovation, trust, and electronic word of mouth are thought to influence tourists' decisions to visit Gemah Tulungagung Beach. While the sampling technique is non-probability sampling by means of purposive sampling where sampling from the population is done randomly and with certain considerations by taking 100 respondents. The results showed that Innovation (X1), Trust (X2) and Electronic Word of Mouth (X3) had a significant effect with the respective values of β were 0.102; 0.478; and 0.691. Keywords: Innovation, Trust, Electronic Word of Mouth, Visit Intention